Molecular phylogeny and morphology reveal a new Lyomyces species (Hymenochaetales, Basidiomycota) from Yunnan Province, China - Jiang, Qianquan; Guo, Wei; Chen, Daxiang; Zhang, Shihui; Zhao, Changlin; Zhou, Hongmin (Phytotaxa, 2025)
The wood-inhabiting fungi play an important role in forest ecosystem processes and functions. Hymenochaetales is one of the fungal orders mainly composed of wood-inhabiting macrofungi within the class Agaricomycetes, Basidiomycota. A new wood-inhabiting fungus, Lyomyces ruiliensis, found in Yunnan Province, Southwestern China, is proposed based on a combination of morphological features and molecular evidence. Lyomyces ruiliensis is characterized by its coriaceous and slightly cracked basidiomata, a monomitic hyphal system with clamped generative hyphae, and ellipsoid basidiospores measuring 4.5–5 × 3–3.5 µm. Phylogenetic analyses of the new species are carried out based on the nuclear ribosomal internal transcribed spacer (ITS) and the nuclear large subunit (nLSU) of ribosomal DNA. Based on the ITS+nLSU sequences, the phylogenetic trees indicate that the new species belongs to the genus Lyomyces, and is retrieved as a sister to L. juniperi. A description, illustrations, and phylogenetic analysis results for the new species are provided. The present study contributes to understanding the species diversity, taxonomy, and phylogeny of Lyomyces in southwestern China.